Prediksi Financial Distress Pada Perusahaan Perkebunan Kelapa Sawit Berbasis Syariah Di Indonesia - TITIK INAYATI; SARAH YULIARINI (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aimed to determine the Financial Distress of Sharia-based oil palm plantation companies in Indonesia. The population of this research is oil palm plantation companies whose data are contained in the Indonesian stock exchange, while the research sample uses the criteria of sharia-based oil palm plantation companies. This company is managed according to sharia and developing its capital in cooperation with sharia banking. The number of research samples is 7 palm oil companies. The data was taken in the 2014-201 period on the Indonesia Stock Exchange. Financial distress using the Altman formula with Z-Score = 3.25+6.56X1 +3.26X2 +6.72X3 + 1.05X4.The results showed (1) Astra Agro Lestari, Tbk (AALI), (2) Austindo Nusantara Jaya (ANNJ) (3) Perkebunan Tinggi Elang, Tbk (BWPT), (4) PP London Sumatra Indonesia, Tbk (LSIP), ( 5) Sampoerna Agro, Tbk (SGRO), (6) Salim Ivomas Pratama, Tbk (SIMP), (7) Sawit Sumbermas Sarana, Tbk (SSMS) in the safe category from bankruptcy. The Palm Oil Company Sumbermas Sarana, Tbk (SSMS) with the average Z-Score calculation shows several 5.8 > 2.60, describing the condition of the company in the safest category from bankruptcy compared to other companies.